2005
DOI: 10.1007/s00280-005-0012-9
|View full text |Cite
|
Sign up to set email alerts
|

Prospective evaluation of carboplatin AUC dosing in patients with a BMI ≥27 or Cachexia

Abstract: When determining the carboplatin dosage from the Calvert formula, there are a lack of data when evaluating patients with cachexia or body mass index (BMI)>or=27. If the Cockcroft and Gault (C-G) creatinine clearance (CrCl) equation is utilized and substituted for glomerular filtration rate in the Calvert formula, the chance for inaccurate dosing occurs especially in these populations. Therefore, the purpose of this study is to evaluate and compare the target carboplatin area under the concentration (AUC) with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
52
1
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(56 citation statements)
references
References 24 publications
2
52
1
1
Order By: Relevance
“…Herrington et al showed in 19 patients with a BMI C 27 kg/m 2 that the use of the adjusted ideal body weight in the Cockcroft-Gault equation led to less bias and more precision than using actual weight [8]. The use of actual weight in obese patients led to an overestimation of the carboplatin clearance and thus carboplatin exposure.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Herrington et al showed in 19 patients with a BMI C 27 kg/m 2 that the use of the adjusted ideal body weight in the Cockcroft-Gault equation led to less bias and more precision than using actual weight [8]. The use of actual weight in obese patients led to an overestimation of the carboplatin clearance and thus carboplatin exposure.…”
Section: Discussionmentioning
confidence: 99%
“…Clinical evidence showed that using actual body weight in the Cockcroft-Gault equation led to an overprediction of the creatinine clearance and, by applying a modified Calvert formula with creatinine clearance as GFR to calculate the dose, produced a higher than expected carboplatin area under the concentrationtime curve [7,8]. Calculation of carboplatin clearance may be more accurate by using other weight descriptors such as fat-free mass or adjusted ideal body weight [8,9]. Since the Cockcroft-Gault equation is widely used in clinical practice for creatinine clearance calculation to be applied in the Calvert formula, there is a risk of significant overdosing of carboplatin in overweight and obese patients.…”
Section: Introductionmentioning
confidence: 99%
“…Scr is dependent on GFR, but its rate of production depends on muscle mass. Because of this, it has been shown that several of the existing formulae overestimate carboplatin CL in both obese patients and patients with cachexia (6). Recently, Thomas et al (7) showed by analyzing the pharmacokinetic data of 45 patients from one center that cystatin C plasma level (cysC) was a marker of carboplatin elimination that is at least as good as Scr.…”
mentioning
confidence: 99%
“…If the patient has a serum creatinine less than 0.8 mg/dL, round the serum creatinine up to 0.8 mg/ dL. 15,16 The Gynecologic Oncology Group has suggested rounding values less than 0.7 mg/dL up to 0.7 mg/dL. The complexity of cancer chemotherapy requires pharmacists be familiar with the complicated regimens and highly toxic agents used.…”
Section: If the Patient Is Not Obese (Body Mass Index [Bmi]mentioning
confidence: 99%
“…If the patient is overweight or obese (BMI ≥ 25), an adjusted body weight (ABW) should be used. 12,13 Although a number of different formulae for calculating ABW are available, the most commonly used formula is: ABW = [(Actual Body Weight -Ideal Body Weight) (0.4)] + Ideal Body Weight. Ideal Body Weight (IBW) is most commonly calculated as 14 : IBW = 50 kg + 2.3 kg/inch > 60 inch (Men); IBW = 45.5 kg + 2.3 kg/inch > 60 inch (Women).…”
Section: If the Patient Is Not Obese (Body Mass Index [Bmi]mentioning
confidence: 99%